DOP12 Non-invasive assessment of intestinal inflammatory activity in Ulcerative Colitis by Multispectral Optoacoustic Tomography (MSOT). (21st January 2022) - Klett, D; Jesper, D; Vitali, F; Federle, A; Atreya, R; Strobel, D; Leppkes, M; Neufert, C; Rath, T; Neurath, M F; Waldner, M J
Abstract: Background: In order to guide therapy in Ulcerative Colitis (UC), repeated determination of intestinal inflammatory activity is essential. Endoscopy is the standard procedure to assess inflammation in UC. However innovative methods for non-invasive, uncomplicated and risk free estimation of inflammatory activity are needed as bowel preparation, patients discomfort and risk of procedural complications limit the (frequent) use of colonoscopy. Multispectral optoacoustic tomography (MSOT) is a promising new method to measure inflammation in UC. Using short and harmless impulses of NIR-lasers, it allows for determination of a specific hemoglobin-signal in the bowel-wall and therefore inflammatory activity in affected bowel segments. However, its informative value in UC has not been evaluated so far. Methods: In 34 patients with confirmed UC, clinical activity parameters (e.g. clinical Mayo-Subscore, B-mode-sonography, C-reactive protein, white blood count) were collected and MSOT of the sigmoid was performed within 2 weeks before/after endoscopy. For MSOT, a commercially available clinical MSOT-system (Acuity Echo, iThera Medical, Munich) was used with sequential analysis of collected data on an external desktop PC. Finally, clinical data, ultrasound findings (Limberg) and MSOT-parameters (single wavelenghts 760 nm, 800 nm, 900 nm; multispectral signals hb, hbO2, hbT) were correlated with endoscopic findings (Mayo endoscopic Subscore, MES). Results: We found strong and significant correlation between MES and MSOT parameters 800 nm (Spearman r = 0, 6599; p < 0, 0001) and HbO2 (Spearman r = 0, 6695; p < 0, 0001), superior to sonographic evaluation of the inflammatory activity in affected bowel segments (Spearman r = 0, 4914; p = 0, 0023). Simultaneously these MSOT parameters demonstrated excellent sensitivity and specifity in distinguishing moderately to highly active (MES 2, 3) from inactive and mild disease (MES 0, 1) (800nm: AUROC 0, 9063 (p < 0, 0001); sensitivity = 93, 75 %, specificity = 88, 89 %; HbO2: AUROC 0, 9063 (p < 0, 0001); sensitivity = 100 %, specificity = 88, 89 %). Conclusion: MSOT is a promising approach to non-invasively assess intestinal inflammation in UC and therefore monitor anti-inflammatory therapy in these patients. Further studies are required to validate these findings.